Towards a Consistent Measurement Stream Processing from Heterogeneous Data Sources - Mario Diván; María de los Ángeles Martín (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this work an updating of the C-INCAMI (Context-Information Need, Concept model, Attribute, Metric and Indicator) conceptual framework for Measurement and Evaluation projects was proposed. The updating incorporated better supporting for the measures stream processing. Therefore, a new version of the measurement interchange schema based on the updated C-INCAMI framework was introduced. This new schema incorporated the concept of “complementary data” linking them with geographic information. The complementary data could be associated with the measures and allowed us incorporating video, geographic information, text plain, audio or pictures with the quantitative measures (deterministic or estimated) jointly. A practical case associated with the Weather Radar of the Experimental Agricultural Station (EAS) INTA Anguil (Province of La Pampa, Argentina) was shown, indicating the advantages of the new schema.